2020
DOI: 10.1038/s41598-020-66630-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals that lung mesenchymal progenitor cells in IPF exhibit pathological features early in their differentiation trajectory

Abstract: In Idiopathic Pulmonary Fibrosis (IPF), there is unrelenting scarring of the lung mediated by pathological mesenchymal progenitor cells (MPCs) that manifest autonomous fibrogenicity in xenograft models. To determine where along their differentiation trajectory IPF MPCs acquire fibrogenic properties, we analyzed the transcriptome of 335 MPCs isolated from the lungs of 3 control and 3 IPF patients at the single-cell level. Using transcriptional entropy as a metric for differentiated state, we found that the leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…4c, Supplementary Materials and Methods). This correlation is consistent with correlation coefficients found in previous publications (ranging from 0.7 to 0.85) 15 and therefore we found good agreement between both experiments. As shown in Supplementary Fig.…”
Section: Plant-nuclei (Pn) Sequencing Of Arabidopsis Thaliana Seedlingssupporting
confidence: 93%
“…4c, Supplementary Materials and Methods). This correlation is consistent with correlation coefficients found in previous publications (ranging from 0.7 to 0.85) 15 and therefore we found good agreement between both experiments. As shown in Supplementary Fig.…”
Section: Plant-nuclei (Pn) Sequencing Of Arabidopsis Thaliana Seedlingssupporting
confidence: 93%
“…Our scRNA-seq data indicate that CD44 is a marker of highly entropic IPF MPCs (10). Based on this information, we first performed IHC double staining of human IPF lung tissue to examine the distribution of CD44 expressing MPCs (double positive for SSEA4 and CD44).…”
Section: Cd44 Expressing Ipf Mpcs Are Present At the Periphery Of The Fibroblastic Focusmentioning
confidence: 99%
“…As an unbiased approach to stratifying the cells, we chose transcriptional network entropy, which serves as a quantitative measure of a cells differentiated state, with higher entropy indicating a less differentiated state (11,12). Our data revealed heterogeneity among IPF MPCs without discrete subpopulations (10). The most highly entropic IPF MPCs displayed the greatest differences in their transcriptional profile compared to control MPCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint efforts through the NHLBI-supported LungMAP program ( https://lungmap.net ) ( 3 ), the Lung Cell Atlas ( 28 ) under the Human Cell Atlas program ( https://www.humancellatlas.org ), and others have utilized these single cell-based technologies to identify remarkable cell heterogeneity throughout lung development ( 9 ) and have discovered new cell types ( 21 ), specific progenitor subgroups ( 37 ), cell differentiation trajectories ( 17 ), and unique abnormal cells during disease pathogenesis ( 4 , 30 ). Recent analyses of human single-cell RNA sequencing (scRNA-seq) data sets have revealed that cell subsets that coexpress ACE2/TMPRSS2 include alveolar type II pneumocytes, absorptive enterocytes, and nasal goblet secretory cells and therefore may serve as cellular targets of SARS-CoV-2 ( 38 ).…”
mentioning
confidence: 99%